Development of Mathematics E-Modules Through the Professional Flip PDF Application Assisted React Strategy to Improve Problem Solving Ability of Vocational Middle School Students Concentration of Accounting Expertise - Dian Kurnianto; Sudiansyah; Heriyanto; Ahmad Yani T.; Bistari (International Journal of Science and Society, 2022)
This study aims to describe the process and results of developing E-teaching modules in the independent learning curriculum through the REACT Strategy (Relating, experiencing, applying, cooperating, and transferring) with the help of professional Flip PDF, for students in Phase E of Accounting Expertise Concentration. In the structure of the independent learning curriculum for Vocational High Schools, there are 2 groups of subjects, namely general subjects (A) and groups of vocational subjects (B). needed by the world of work, mastering science and technology, arts and culture. E-module development using the ADDIE model with the stages of development: Analysis, Design, Development, Implementation, and Evaluation. The resulting product is a mathematics e-module with the REACT Strategy assisted by a professional flip pdf application that can be accessed by students using Android. Based on the results of utilization in the field, the resulting E-module can improve the problem-solving ability of students. This e-module with the REACT strategy assisted by flip PDF is feasible to be used as an alternative in mathematics learning, especially to familiarize students with being able to define problems, diagnose problems, formulate alternative strategies, choose alternative strategies and evaluate in mathematics lessons that incorporate technology. Based on the results of 28 students' answers to banking math problems in the e-module, the average score is 61.78 with a percentage score of 77.23% with a high category.